Mass Solitary and Mass Incarceration: Explaining the Dramatic Rise in Prolonged Solitary in America's Prisons - Jules Lobel (2020)
In the last two decades of the twentieth century, prisons throughout the United States witnessed a dramatic rise in the use of solitary confinement, and the practice continues to be widespread. From the latter part of the nineteenth century until the 1970s and ’80s, prolonged solitary confinement in the United States had fallen into disuse, as numerous observers and the United States Supreme Court recognized that the practice caused profound mental harm to prisoners. The reasons for this dramatic rise in the nationwide use of solitary confinement and the development of new supermax prisons have not been explored in depth. In particular, there has been little critical discussion of the rise of mass prolonged solitary as a product of the mass incarceration of the last several decades of the twentieth century. This Essay locates the rise of mass solitary in the 1980s in the context of mass incarceration. It explains the dramatic expansion of the use of solitary confinement and the construction of new super-maximum (supermax) prisons as an attempt by prison officials and politicians to maintain control of prisons in the face of increasingly radicalized, rebellious prisoners—often, but not exclusively, African-American—who had organized protests and disobedient conduct in American prisons from the 1960s to the 1980s. The rise of solitary was connected to the use of mass incarceration as a form of social control. As society became more violent, so too did many prisons, but to view that violence as the underlying cause of the growth of supermax and other segregated confinement obscures the deeper, underlying causes of the rise of mass solitary. Those causes are linked to the rise of mass incarceration itself. Uncovering the history and causes of the dramatic rise in supermax prisons and the use of prolonged solitary confinement in the 1980s and ’90s is critical to understanding not only how we got to where we are, but how we can end this cruel and inhumane practice. The first Part of this Essay recounts the origins of the supermax prison at Marion Federal Penitentiary in the late 1970s and early 1980s and demonstrates that the rise of mass solitary was more an official reaction to the need to control politically active and disruptive prisoners than to the violence narrative. The second Part explores prison officials’ need to reassert control over their prisoners and draws the parallels between the rise of both mass incarceration and mass solitary as a racialized mechanism of social control. The third Part introduces the preventive paradigm as a model to control prisoners and demonstrates that the concept of preventing future misconduct fueled both mass incarceration and the modern supermax, resulting in minimizing due process restraints and erroneously isolating thousands of people. Finally, the last Part analyzes the current reform movement and the alternatives that have been proffered and utilized to replace solitary, supermax confinement. The Essay concludes that prolonged solitary confinement can be abolished, and that prison officials have alternatives that can safely manage even very dangerous prisoners